2015
DOI: 10.1007/s13197-015-2019-5
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of annatto (Bixa orellana L.) seed separator machine

Abstract: A small, continuous power operated machine with a capacity of 132 kg/h was designed, fabricated and evaluated its performance for separation of annatto (Bixa orellana L.) seeds from freshly harvested pods. Physical and engineering parameters of annatto pods and seeds were evaluated to design a machine. The densities of pod, seed, and husk are 134.7 to 186.0 kg/m 3 , 1206 to 1253.9 kg/m 3 , 317 to 381.4 kg/m 3 respectively. The moisture content of seeds were in the range 18.83 -20.1 % (db) and pod 8 to 10 % (db… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
(13 reference statements)
7
5
0
2
Order By: Relevance
“…This agreed with the findings of Atiku, Aviara, and Haque () who reported that the percentage seed damage of Bambara groundnut increased with increased moisture content to a maximum value. This implies that moisture content has significant effect on dehulling process, which supports the findings of Ndukwu and Asoegwu (), Pradhan et al (), Gitau et al (), Atiku et al (), Sobowale, Adebiyi, and Adebo () and Math et al ().…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This agreed with the findings of Atiku, Aviara, and Haque () who reported that the percentage seed damage of Bambara groundnut increased with increased moisture content to a maximum value. This implies that moisture content has significant effect on dehulling process, which supports the findings of Ndukwu and Asoegwu (), Pradhan et al (), Gitau et al (), Atiku et al (), Sobowale, Adebiyi, and Adebo () and Math et al ().…”
Section: Resultssupporting
confidence: 85%
“…At higher moisture content levels, moringa seeds are supple, which makes it difficult to dehull. This was consistent with the observations ofOluwole, Abdulrahim, and Olalere (2007) on bambara groundnut shelling where the highest shelling efficiency was obtained at the lowest moisture content,Pradhan et al (2010) on jatropha dehulling where a decreasing trend in dehulling efficiency with increased moisture content was observed,Gitau, Mboya, Njoroge, and Mburu (2013), which reported that shelling efficiency increased with decrease in moisture content for all the groundnut varieties studied, andMath, Ramesh, Nagender, and Satyanarayana (2016), which observed decreased dehulling efficiency as moisture content of annatto pod increased. At lower moisture content, there was comparatively high recovery of fully dehulled whole seeds.…”
supporting
confidence: 91%
“…The pulping efficiency of the experimental bench device was similar to that found in a prototype for extraction of Bixa orellana L. pulp that was developed by Math et al (2016), which had efficiency of 92.3%. A device built by Sharma, Pradhan, Naik, Bhatnagar and Singh, (2013), for pulping Aleurits fordii had efficiency of 74.6%.…”
Section: Results Of Performance Evaluation Of the Machinesupporting
confidence: 68%
“…For example: Jarimopas and Ruttanadat (2007), developed a prototype for trimming green coconut (Cocos nucifera) shells, and Raji and Olofin, (2011), designed and fabricated a device to extract proteins from pumpkin (Telfairia occidentals) leaves for human consumption in African communities. In addition, Owolarafe, Adetan, Olatunde, Ajayi, and Okoh (2013), developed and evaluated a process to peel carob (Parkia biglobosa); Obayopo, Taiwo, Owolarafe, and Adio (2014), designed a compact device to slice banana (Musa paradisiaca L.); and Math, Ramesh, Nagender, and Satyanarayana (2016), designed, fabricated, and evaluated a bench device to extract urucum (Bixa orellana L.) pulp.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, four concave clearances such as 10, 13, 16, and 19 mm have chosen to evaluate maximum efficiency. Equations 1–8 were used to determine various dimensions for different components of the seed decorticator (Atiku et al, ; Fadele & Aremu, ; Ishola et al, ; Math et al, ; Oluwole et al, ; Raghtate & Handa, ; Sobowale et al, ). V= 13πr2h P=2πNT Mc= P12×|l2×r2normall2+r2 MR=16×f×t2×normall2+r2 M= W×normall8 Te=true(M2+T2true)1/2 …”
Section: Materials and Methodologymentioning
confidence: 99%